2023
DOI: 10.1002/adfm.202305965
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Solid Solution MXene for Low‐Dosage NIR‐II Tumor Photothermal Therapy

Xinfeng Tang,
Yanhua Zhu,
Delong Duan
et al.

Abstract: Due to the deep biological penetrability and therapeutic depth, the photothermal therapy over second near‐infrared region (NIR‐II) is booming against deep‐seated tumors. Intensive endeavors are committed to looking for suitable photothermal agents (PTAs), but the progress seems not so satisfied toward the choice of PTA dosage. Herein, a comprehensive parameter, incident photon‐to‐thermal conversion coefficient (IPTCE), is used to evaluate the overall conversion of PTAs at different dosage, which will benefit f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…These results suggested that the 1060 nm laser had better tissue penetration capacity compared to the 808 nm laser, as it experienced less photothermal attenuation when penetrating tissues of the same thickness. 35 Furthermore, the Nb 2 C nanosheets irradiated with a 1060 nm laser showed a higher temperature than that with an 808 nm laser (Figure 3B). The temperature of the Nb 2 C nanosheets increased with the concentration and irradiation power density increase, indicating the photothermal property of Nb 2 C nanosheets was concentration-dependent and power-dependent (Figure 3C, D).…”
Section: Photothermal Performance and Drugmentioning
confidence: 94%
See 1 more Smart Citation
“…These results suggested that the 1060 nm laser had better tissue penetration capacity compared to the 808 nm laser, as it experienced less photothermal attenuation when penetrating tissues of the same thickness. 35 Furthermore, the Nb 2 C nanosheets irradiated with a 1060 nm laser showed a higher temperature than that with an 808 nm laser (Figure 3B). The temperature of the Nb 2 C nanosheets increased with the concentration and irradiation power density increase, indicating the photothermal property of Nb 2 C nanosheets was concentration-dependent and power-dependent (Figure 3C, D).…”
Section: Photothermal Performance and Drugmentioning
confidence: 94%
“…4,32−34 The deeper tissue penetration and higher maximum permissible exposure (MPR) in the NIR-II biowindow offer the potential for clinical tumor treatment without causing side effects. 35,36 The construction of Nb 2 Cbased nanocomposite system has led to the development of various new treatment methods, such as PTT/chemotherapy (CHT) combined therapy, 37,38 PTT/CDT combined therapy, 34,39 and PTT/immunotherapy (IT) combined therapy. 40 Herein, the novel active targeted multifunctional nanomedicine Nb 2 C-PAA-DOX@Apt-M (NDA-M) has been fabricated for combined tumor therapy (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, endeavors to augment the efficacy of AuNRs and drugs in cancer through the photothermal effect of laser irradiation have been steadily progressing . Furthermore, diverse examinations involving heat generated by gold irradiated with NIR and ultraviolet (UV) rays are ongoing in the medical field. Based on these studies, gold nanorods and DX were synthesized in this study, and their therapeutic potential in skin inflammation was examined by irradiating them with a gold-reactive laser.…”
Section: Introductionmentioning
confidence: 99%
“…In the MAX structure, M represents an early transition metal, A represents aluminum or silicon, and X is carbon or nitrogen. 22 Owing to their large surface area, wide absorption range, superior conductivity, and favorable hydrophilicity, 23,24 MXenes are widely used in energy storage, 25 biomedicine, 26 and sensing. 27 MQDs prepared by acid oxidation and hydrothermal synthesis not only inherit the advantages of their precursor MXenes, including the relatively high surface area, and wide absorption range, but also the properties of QDs, such as the excellent dispersion, sensitive terminating groups, and excellent optical properties.…”
Section: Introductionmentioning
confidence: 99%